COLOUR DETECTOR TOOL USING TCS3200 AND ARDUINO UNO FOR BLIND AND CHILD - Mohamad Habib Ahsan; Arief Marwanto; Agus Suprajitno (Universitas Islam Sultan Agung, 2018)
Color detector using TCS3200 that can help the independence of the blind category of low vision in daily life and help improve children’s enthusiasm for learning colors early age. Creation tool TCS3200 color detection is based on the large number of persons with special needs, so this tool can be independent again in everyday life, esppecially on matters relating to the colors. The method used is a model of research and development, starting from planing concept and manufacture of hardware product design to final testing tools as well as the customization tools. The results show that the prototype device is able to conduct perform color detector recognize by voice. For the blind peoples, the prototype of color detection is able perform well by expresse the statement of 80%, whenever the juvenile has state that prototype is able to perform color detection is 70%.Color detector using TCS3200 that can help the independence of the blind category of low vision in daily life and help improve children’s enthusiasm for learning colors early age. Creation tool TCS3200 color detection is based on the large number of persons with special needs, so this tool can be independent again in everyday life, esppecially on matters relating to the colors. The method used is a model of research and development, starting from planing concept and manufacture of hardware product design to final testing tools as well as the customization tools. The results show that the prototype device is able to conduct perform color detector recognize by voice. For the blind peoples, the prototype of color detection is able perform well by expresse the statement of 80%, whenever the juvenile has state that prototype is able to perform color detection is 70%.